+0  
 
0
302
1
avatar

x^(2) - 6x = 1/2x + 42

Find x

Guest Aug 16, 2017
 #1
avatar+333 
0

For this, we need to transorm the eq. to standard form:

\(x^2-6x=\frac{1}{2}x+42\)

\(x^2-\frac{13}{2}x-42=0\)

Now to use the quadratic formula:

\(a=1\)

\(b=-\frac{13}{2}\)

\(c=-42\)

\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)

\(x = {-(-\frac{13}{2}) \pm \sqrt{(\frac{13}{2})^2-4(1)(-42)} \over 2(1)}\)

\(x = \frac{\frac{13}{2} \pm \sqrt{210+{1 \over 4}}}{2}\)

\(x = {{13 \over 2}\pm(14+{1 \over 2})\over 2}\)

\(x = {10+{1\over2}, -4}\)

 

laugh

Mathhemathh  Aug 16, 2017

9 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.